Aspirin versus anticoagulation in intra‐ and extracranial vertebral artery dissection. Issue 1 (20th July 2012) - Arauz, A.; Ruiz, A.; Pacheco, G.; Rojas, P.; Rodríguez‐Armida, M.; Cantú, C.; Murillo‐Bonilla, L.; Ruiz‐Sandoval, J. L.; Barinagarrementeria, F.
Abstract : Background and purpose: To evaluate the incidence and predictors of ischaemic recurrent stroke and the adverse events of antithrombotic therapy in patients with first intra‐ or extracranial vertebral artery dissection (VAD) who were treated with aspirin or oral anticoagulation (OA). Methods: A 21‐year database of consecutive patients with confirmed diagnoses of VAD ( n  = 110, 63% men; mean age 37.9 ± 8.5 years) without intracerebral hemorrhage and who were treated with aspirin or OA were analyzed retrospectively. In all cases, the admission diagnosis was ischaemic stroke. Three groups were defined according to the site of the dissection: (i) extracranial, (ii) intracranial, and (iii) intra‐/extracranial. Clinical follow‐up was obtained by neurologic examination. Outcome measures were (i) recurrent ischaemic events (ischaemic stroke or transient ischaemic attack) and (ii) intra‐ and extracranial major bleeding. Results: No difference in age, smoking, or hypertension was found between patients treated with OA ( n  = 49) and those treated with aspirin ( n  = 50). Extracranial artery dissection (49%) had preponderance over intracranial (27%) or intra‐/extracranial (23%) location. During the follow‐up, recurrent ischaemic events were rare (one case). There were no bleeding complications. The treatment that was used did not influence the functional outcome or recanalization. A good functional outcome (modified Rankin score ≤ 2) was observed in 82 patients. Conclusions: Although this was a non‐randomized study, our data suggest that the frequency of recurrent ischaemic stroke in patients with intra‐ or extracranial VAD is low and most likely independent of the type of antithrombotic treatment.